2015
DOI: 10.1016/j.jacep.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, Prognosis, and Electrophysiological Mechanisms of Atrial Arrhythmias After Lung Transplantation

Abstract: Objective To investigate incidence and timing, risk factors, prognostic significance, and electrophysiological mechanisms of atrial arrhythmia (AA) after lung transplantation. Background Although new-onset AA is common after thoracic surgery and is associated with poorer outcomes, prognostic and mechanistic data is sparse in lung transplant populations. Method A total of 293 consecutive isolated lung transplant recipients without known AA were retrospectively reviewed. Mean follow-up was 28±17 months. Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 21 publications
2
51
2
Order By: Relevance
“…The PRISMA flow diagram detailing the disposition of retrieved publications is shown in Figure . Nine studies were included in our final analysis, yielding a total of 2653 patients (Table ). Of these, 791 had postoperative AAs, giving an overall incidence of 29.8%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flow diagram detailing the disposition of retrieved publications is shown in Figure . Nine studies were included in our final analysis, yielding a total of 2653 patients (Table ). Of these, 791 had postoperative AAs, giving an overall incidence of 29.8%.…”
Section: Resultsmentioning
confidence: 99%
“…The peak onset of AAs after lung transplant varied from 2 to 7 days. Of note, five studies grouped atrial fibrillation and atrial flutter together, with a combined incidence of 31.8% (487/1532). Four studies divided AAs into atrial fibrillation (AF) and atrial flutter/supraventricular tachycardia (AFL/SVT) and found a total incidence of AAs of 27.1% (304/1121), of which 89.1% (271/304) were AF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung transplantation (LT) has been performed increasingly over the past 2 decades [1,2]. Atrial arrhythmias (AA), including atrial fibrillation (AF), atrial flutter (AFL), and atrial tachycardia (AT), are highly prevalent complications after LT, with a reported incidence ranging from 25% to 45% depending on their definition and methods of detection [3][4][5][6][7][8][9]. At present, there is inconsistent evidence supporting the association between mortality after LT and postoperative AA [3,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting subset of lung transplant patients may have atrial tachycardias using donor-to-recipient conduction across an anastomotic line. This has been supported by 2 case reports [3,15] but disputed by some studies including a series of 25 patients in whom electrophysiological mapping showed that all PV antral arrhythmias arose from recipient not donor myocardium [16]. …”
mentioning
confidence: 95%